KESANTUNAN SAPAAN PENGANTAR KONSULTASI TUGAS PERKULIAHAN BAHASA INDONESIA SECARA DARING MAHASISWA FAKULTAS KEDOKTERAN UNIVERSITAS MUHAMMADIYAH PALEMBANG - Houtman, Houtman (LPPM STKIP PGRI Bandar Lampung, 2021)
Politeness in language is very necessary in communicating. By having polite language besides one's relationship can be better, one's heart will not be hurt by listening to the spoken words. The formulation of the problems in this study are: 1) What is the expression in the greeting of students to lecturers through the WhatsApp social media? 2) To what extent does the utterance include positive politeness and negative politeness? This study aims to describe politeness in the use of student greetings to lecturers during lecture assignment guidance interactions. Data collection was carried out through field research using a sociolinguistic approach. The research method used is the observation method and the method of observation using the technique of free listening proficiently, note-taking techniques and recording techniques. Data were analyzed descriptively. The population of this study were all greeting speeches of students in the Faculty of Medicine (FK) Universitas Muhammadiyah Palembang. The sample of this research is a number of utterances which are considered to represent the first semester students in FK. The results showed that there were four forms of use of the principle of politeness. From this study it was found that the average student was good at placing utterances that should be spoken to the lecturer. Besides that, it was also found that sometimes students seemed to be pushy in asking for a response from the lecturer. This is certainly not polite to do especially in an academic environment. In this study, more positive politeness was found.